2008
DOI: 10.1088/0268-1242/23/12/125003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrodeposited and sputtered intrinsic and aluminium-doped zinc oxide thin films

Abstract: Intrinsic zinc oxide (i-ZnO) and aluminium-doped ZnO (ZnO:Al) are components of high-efficiency copper indium gallium diselenide solar cells. This paper examines both of these materials grown by two different techniques, namely radio frequency sputtering and electrodeposition (ED) for comparison and a better understanding. X-ray diffraction showed all materials to be polycrystalline and hexagonal (wurtzite) ZnO. Scanning electron microscopy indicated crystallites with different orientations for ED materials co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Thus, this result concorded with the best photoconductivity 400 ( cm) −1 [31] and high transmittance equals to 100% in visible range for IZO/glass [33].…”
Section: Structural Characterizationssupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, this result concorded with the best photoconductivity 400 ( cm) −1 [31] and high transmittance equals to 100% in visible range for IZO/glass [33].…”
Section: Structural Characterizationssupporting
confidence: 71%
“…The starting material used was zinc acetate dihydrated, Zn (CH3COO)2·2H2O) [30,31]. Doping sources were aluminium nitrate nonahydrated (Al (NO3)3·9H2O) and indium(III) chloride (InCl3) [11,12,30].…”
Section: Methodsmentioning
confidence: 99%
“…An electroless -chemical process is proposed, consisting in the formation of the super oxide radical (O cations. (Wellings et al, 2008) have deposited ZnO thin films from aqueous zinc nitrate solution at 80ºC onto fluorine doped tin oxide (FTO) coated glass substrates. Structural analysis, surface morphology, optical studies and electrical conductivity were studied and thickness of the ZnO films was found to be 0.40 μm.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose has been the preparation of transparent front contact layers in CIGS and CdTe solar cells. Higher conductivity of these layers has been achieved by incorporation of B [61,62], Al [63,64] or In [63,65] during electrodeposition of ZnO from aqueous zinc nitrate solution, by addition of dimethylamine borane, aluminum trichloride or indium nitrate to the electrodeposition bath. For moderate doping levels of 1-2%, the typical hexagonal crystal structure of ZnO is preserved in the obtained materials.…”
Section: Electrodeposition Of Doped Znomentioning
confidence: 99%
“…In fact, front contact layers in CIGS and CdTe solar cells are usually still made by gas-phase methods, such as electron-beam evaporation [78] or sputtering [64,79] for this reason. For the same reason, only few studies exist in which electrodeposited ZnO films have been used as a component in p-n bulk heterojunctions.…”
Section: P-n-junctions Based On Electrodeposited Znomentioning
confidence: 99%